1969
DOI: 10.1139/v69-380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen bonding and homoconjugation on the titration curves of a synthetic polynuclear phenolic compound in non-aqueous solvents

Abstract: A straight chain polynuclear phenolic compound containing 9 phenolic nuclei has been synthesized and titrated in several non-aqueous solvents. In some of the solvents, a stepwise neutralization of OH groups in the compound has been observed. Some of the OH groups in the compound have a hyperacid character, and a sharp increase in conductance was observed as these OH groups are neutralized by the base. Some of these features have been discussed in terms of intramolecular hydrogen bonding and homoconjugation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1970
1970
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…The potentiometric curves, however, showed only two to three inflections, indicating that some of the hydroxyl groups on each chain are hyperacidic, while others have roughly the same acidity. A similar study of a nonameric phenolic compound showed as well that the hydroxyl groups are neutralized in mostly a stepwise manner in the conductometric titration, whereas they are lumped together in the potentiometric titration …”
Section: Pk a Estimationmentioning
confidence: 91%
See 1 more Smart Citation
“…The potentiometric curves, however, showed only two to three inflections, indicating that some of the hydroxyl groups on each chain are hyperacidic, while others have roughly the same acidity. A similar study of a nonameric phenolic compound showed as well that the hydroxyl groups are neutralized in mostly a stepwise manner in the conductometric titration, whereas they are lumped together in the potentiometric titration …”
Section: Pk a Estimationmentioning
confidence: 91%
“…A similar study of a nonameric phenolic compound showed as well that the hydroxyl groups are neutralized in mostly a stepwise manner in the conductometric titration, whereas they are lumped together in the potentiometric titration. 20 Chatterjee attributes this difference to homoconjugation, which potentiometry cannot detect. Later studies considered the influence of additional functional groups on the acidity of novolac-like oligomers.…”
Section: Pk a Estimationmentioning
confidence: 99%
“…Correlation between the charge on the phenolate oxygen and the pKa of the corresponding phenols for a group of substituted phenols, measured in water and in DMSO. 10,11 [q] dimer ) -1 / 2 (0.58 + 0.32) ) -0.45 The one-dimensional Schroedinger equation was solved using this potential and an effective mass taken to be that associated with the proton in the fictitious vibration in the transition state, 1.1610 amu. The potential energy function and the wave function solutions are presented in Figure 6.…”
Section: Frequency Of Intramolecular Proton Transfermentioning
confidence: 99%
“…The effect of hydrogen bonding on acid-base equilibria in nonaqueous solvents has been discussed (43,94,137).…”
Section: Solvent Phenomenamentioning
confidence: 99%